The Metabolic Syndrome Pharmacology and Clinical Aspects - Beck-Nielsen, Henning; SpringerLink (Online service) (Vienna : Springer Vienna : Imprint: Springer, 2013)
Metabolic syndrome is a common syndrome affecting about 20% of the adult population in Europe, and the prevalence is likely similar in other industrialised countries worldwide. It is mainly caused by the western lifestyle, which tends to produce abdominal obesity, but a genetic predisposition also plays a part. This syndrome, which is linked to leisure lifestyles and overeating/obesity, can develop into type 2 diabetes, cardiovascular disease and cancer. Therefore, proper treatment and prevention are essential. This book discusses lifestyle intervention and treatment, specifically with pharmacological compounds, in order to formulate a strategy for treating the metabolic syndrome in daily practice.
Keywords: Medicine; Toxicology; Diabetes; Endocrinology; Metabolic diseases; Medicine & Public Health; Metabolic Diseases; Pharmacology/Toxicology.; Endocrinology; Diabetes